[ClP(μ-PMes*)]2—A versatile reagent in phosphorus chemistry. (2nd April 2016) - Bresien, Jonas; Schulz, Axel; Villinger, Alexander
GRAPHICAL ABSTRACT: ABSTRACT: The synthesis and some key reactions of the cyclotetraphosphane [ClP(μ-PMes * )]2 (2, Mes * = 2, 4, 6-tri-tert-butylphenyl) with Lewis acids and reducing agents are discussed. All products were fully characterized, including single crystal X-ray diffraction, spectroscopic methods as well as computational studies.